Quantifying DNA replication speeds in single cells by scEdU-seq - Berg, Jeroen van den; van Batenburg, Vincent; Geisenberger, Christoph; Tjeerdsma, Rinskje B.; Jaime-Soguero, Anchel de; Acebron, Sergio P.; van Vugt, Marcel A. T. M.; van Oudenaarden, Alexander (Nature methods, 2024)
In a human cell, thousands of replication forks simultaneously coordinate duplication of the entire genome. The rate at which this process occurs might depend on the epigenetic state of the genome and vary between, or even within, cell types. To accurately measure DNA replication speeds, we developed single-cell 5-ethynyl-2'-deoxyuridine sequencing to detect nascent replicated DNA. We observed that the DNA replication speed is not constant but increases during S phase of the cell cycle. Using genetic and pharmacological perturbations we were able to alter this acceleration of replication and conclude that DNA damage inflicted by the process of transcription limits the speed of replication during early S phase. In late S phase, during which less-transcribed regions replicate, replication accelerates and approaches its maximum speed.